Characterization of Integrons and Quinolone Resistance in Clinical Escherichia coli Isolates in Mansoura City, Egypt - Shaymaa H. Abdel-Rhman; Rehab M. Elbargisy; Dina E. Rizk (International Journal of Microbiology)
Escherichia coli is a common pathogen in both humans and animals. Quinolones are used to treat infections caused by Gram-negative bacteria, but resistance genes emerged. Only scarce studies investigated the association between plasmid-mediated quinolone resistance (PMQR) genes and integrons in clinical isolates of E. coli. The current study investigated the prevalence of quinolone resistance and integrons among 134 clinical E. coli isolates. Eighty (59.70%) isolates were quinolone-resistant, and 60/134 (44.77%) isolates were integron positive with the predominance of class I integrons (98.33%). There was a significant association between quinolone resistance and the presence of integrons (P<0.0001). Isolates from Urology and Nephrology Center and Gastroenterology Hospital were significantly quinolone-resistant and integron positive (P≤0.0005). Detection of PMQR genes on plasmids of integron-positive isolates showed that the active efflux pump genes oqxAB and qepA had the highest prevalence (72.22%), followed by the aminoglycoside acetyltransferase gene (aac(6′)-Ib-cr, 66.67%) and the quinolone resistance genes (qnr, 61.11%). Amplification and sequencing of integrons’ variable regions illustrated that no quinolone resistance genes were detected, and the most predominant gene cassettes were for trimethoprim and aminoglycoside resistance including dfrA17, dfrB4, and dfrA17-aadA5. In conclusion, this study reported the high prevalence of PMQR genes and integrons among clinical E. coli isolates. Although PMQR genes are not cassette-born, they were associated with integrons’ presence, which contributes to the widespread of quinolone resistance in Egypt.